Factors of agricultural growth in West Africa : proceedings of an international conference held at Legon, April 1971 - Ofori, Isaac M.; University of Ghana (Legon : Institute of Statistical, Social and Economic Research, University of Ghana, 1973)
The conference brought out clearly the need for a multi or inter disciplinary approach to the study of agricultural growth as well as the development of interterritorial links
Includes bibliographical references.
obn 22/01/2019
Loans
Keywords: Agriculture and state; Agriculture